A Profile of Patients on ASA or NSAIDs Hospitalized with Gastrointestinal Perforations - James D Bailey; Robert J Bailey; Richard N Fedorak (Canadian Journal of Gastroenterology)
BACKGROUND: In a recent clinical trial gastrointestinal tract perforations in patients on nonsteroidal anti-inflammatory drugs (NSAIDs) were found to occur with a frequency of 0.15%, and possibly to be reduced in patients concomitantly using the cytoprotective agent misoprostol.